PENGARUH INOKULASI RHIZOCTONIA BINUKLEAT (BNR) DAN VARIASI PENYIRAMAN TERHADAP KADAR NITROGEN, POSFOR TANAH DAN PERTUMBUHAN VANILI (Vanilla planifolia Andrews. ) - D. DARYANTI; H. HARYUNI (JURNAL ILMIAH AGRINECA, 2017)
This study aims to determine the effect of inoculation of Rhizoctonia Binukleat (BNR) and watering variation. This study used a factorial completely randomized design consisting of 2 treatments inoculated with Rhizoctonia binucleic fungi. And not inoculated, the second factor of the watering interval is that every (1, 5, 10, 15) days, there are 8 treatment combinations, each treatment is repeated 3 times. The results showed that 1). Inoculation of R binucleic and watering time interval had no significant effect on soil N content but had significant effect on soil P level that was able to increase P level of soil, 2). Rinukleat inoculation R and watering time interval significantly affect plant height, leaf number and fresh weight of stover 3). Inoculation of R binucleic acid can increase plant height, leaf number and fresh weight, 4). The combination of inoculation of R binucleic and watering time interval did not give real interaction to soil N and P as well as to plant height, leaf number and weight of fresh stover.